Shaping and Optimizing the Image of Virtual City Spokespersons Based on Factor Analysis and Entropy Weight Methodology: A Cross-Sectional Study from China - Jialing Chen; Linfan Pan; Ren Zhou; Qianling Jiang (Systems, 2024)
With the continuous development of digital technology, the widespread use of virtual spokespersons to promote city images is becoming increasingly prevalent. This study responds to this trend by employing a factor analysis and entropy weight methodology to explore the different dimensions and priorities in shaping the image of virtual city spokespersons in China. The aim is to offer insights into the design strategies and directions for shaping the image of virtual city spokespersons. For the research, we first conducted a literature review and semi-structured interviews to investigate the requirements of users in mainland China and Hong Kong regarding the image shaping of virtual city spokespersons. Building upon this groundwork, a questionnaire was designed and distributed, and it successfully gathered 512 valid responses. Subsequently, a factor analysis was utilized to identify eight key dimensions in shaping the images of Chinese virtual city spokespersons: “Design elements”, “Anthropomorphism”, “Evolutionary”, “Emotionalization”, “Narrativity”, “Culturalism”, “Interactivity”, and “Reliability”. Then, the entropy weighting method was applied to analyze the weights of each indicator within these dimensions. The results revealed that “Design elements” have the highest priority in shaping the image of virtual city spokespersons, followed by “Anthropomorphism”, “Emotionalization”, “Evolutionary”, “Culturalism”, “Narrativity”, “Reliability”, and “Interactivity”. Based on these findings, a series of design optimization strategies are proposed, including but not limited to shaping visually appealing images aligned with user perceptions, establishing emotional connections with users, and meeting the functional experience needs of users. These strategies not only contribute to the image shaping of virtual city spokespersons, but also provide vital guidance for innovative directions in promoting the publicity and marketing of Chinese cities.